Characterization of an electrostatic filter prototype for bioaerosol flowmetering for INTA Investigation Aerial Platforms. (August 2019) - Sor, Suthyvann; Bardera, Rafael; Garcia-Magariño, Adelaida; Gonzalez, Elena; Aguilera, Ángeles
Abstract: The characterization of the airborne microorganisms at different altitudes of the atmosphere is usually conducted by means of aerial platforms. It is very interesting to know the biological processes in the atmosphere. However, there are problems associated to the fact that sampling systems are embarked on an aircraft and the low presence of microorganisms at high altitude. A prototype of a new electrostatic filter for bioaersol flowmetering dedicated to biology investigations has been developed. This prototype was designed to be installed on board in aerial platforms of INTA. The experimental characterization of the aerodynamic flow was performed in order to investigate the behaviour of the filter when different air intake widths and different mechanical deflectors are employed. A combination of these impactor with the filters based on industrial electrostatic precipitator technology have been studied. Non-intrusive Particle Image Velocimetry technique has been used to measure the flow field inside the filter when it was running under controlled conditions in laboratory. This study is a first investigation on the flow field of filter for bioaerosol flowmetering to be embarked on an aircraft. The results show the influence of each parameter in the flow field that could be used for further investigations and designs. Highlights: A prototype of a new electrostatic filter for bioaersol flowmetering dedicated to biology investigations has been developed. This prototype was designed to be installed on board aerial platforms of INTA. Experimental characterization of the aerodynamic flow was performed using PIV. The results could be used for industrial purposes in collecting data on aerial platforms.